Latent autoimmune diabetes in adults: A distinct but heterogeneous clinical entity - Nambam, Bimota (Baishideng Publishing Group Co., Limited, 2010)
Latent autoimmune diabetes in adults (LADA) accounts for 2%-12% of all cases of diabetes. Patients are typically diagnosed after 35 years of age and are often misdiagnosed as type II Diabetes Mellitus (DM). Glycemic control is initially achieved with sulfonylureas but patients eventually become insulin dependent more rapidly than with type II DM patients. Although they have a type II DM phenotype, patients have circulating beta (β) cell autoantibodies, a hallmark of type I DM. Alternative terms that have been used to describe this condition include type 1.5 diabetes, latent type I diabetes, slowly progressive Insulin Dependent Diabetes Mellitus, or youth onset diabetes of maturity. With regards to its autoimmune basis and rapid requirement for insulin, it has been suggested that LADA is a slowly progressive form of type I DM. However, recent work has revealed genetic and immunological differences between LADA and type I DM. The heterogeneity of LADA has also led to the proposal of criteria for its diagnosis by the Immunology of Diabetes Society. Although many workers have advocated a clinically oriented approach for screening of LADA, there are no universally accepted criteria for autoantibody testing in adult onset diabetes. Following recent advances in immunomodulatory therapies in type I DM, the same strategy is being explored in LADA. This review deals with the contribution of the genetic, immunological and metabolic components involved in the pathophysiology of LADA and recent approaches in screening of this distinct but heterogeneous clinical entity.